Image Encryption-Then-Transmission Using DNA Encryption Algorithm and The Double Chaos - Xing-Quan Fu; Bo-Cheng Liu; Yi-Yuan Xie; Wei Li; Yong Liu (IEEE Photonics Journal, 2018)
According to the DNA encryption algorithm and the double-chaotic system which contains the optical chaos and the coupled map lattice chaotic system, a novel image encryption-then-transmission system is proposed. In the system, with identical chaotic injection from a master laser with two optical feedbacks, two slave lasers (SL1 and SL2) can output similar chaotic signals served as chaotic carrier to transmit image and used to generate the core part of the encryption scheme. A 128-b key is selected to generate the original value of the double-chaotic system, which decides the DNA complementary rule, hence, the key is hypersensitive in encryption and decryption process. The security analysis demonstrates the effectiveness of the proposed encryption system. The simulation results verify that the cryptosystem is enough against the traditional attacks, such as statistical attack, differential attack, brute force attack, and entropy attack. Moreover, the encrypted image can be the optical message and transmitted in 10 km single-mode fiber channel from SL1 to SL2. In order to ensure the security, we use the chaos masking technique to modulate and demodulate the optical message. Through numerical simulations of the cross-correlation function, the chaos synchronization between SL1 and SL2 is desired. The Q-factor is 9.559 and the bit error rate is $5.771× 10^{-22}$ .